Influence of Fasting followed by Acute Water Ingestion on Subfoveal Choroidal Thickness in Eyes of Healthy Subjects. Issue 1 (2017) - Blanco-Garavito, Rocio; Astroz, Polina; Yves Cohen, Salomon; Souied, Eric H.
Purpose: To investigate the influence of at least 12 hours of fasting followed by acute water ingestion on macular choroidal thickness in eyes of healthy subjects. Methods: Prospective case series study including healthy volunteers from April 1, 2015 to May 31, 2015. Macular choroidal thickness was measured on enhanced depth imaging optical coherence tomography (EDI-OCT) and on swept-source (SS)-OCT after 12 hours of fasting, and 60 minutes after acute water ingestion (750 mL in 5 minutes). Results: A total of 52 eyes of 26 healthy volunteers were included in this study. The mean age for participants was 32 years old. After 12 hours of fasting, the mean (±SD) subfoveal choroidal thickness was 335.43 (±104.82) μm on EDI-OCT and 286.16 (±80.32) μm on SS-OCT. The mean (±SD) subfoveal choroidal thickness after acute water intake was 352.32 (±120.36) μm and 290.5 (±85.86) μm, respectively. There was no significant difference between the mean subfoveal thickness at baseline and 60 minutes after acute water ingestion for any of the choroidal imaging techniques (p = 0.1386 for EDI-OCT and p = 0.0659 for SS-OCT). Conclusions: These results suggest that choroidal circulation can physiologically quickly adapt to systemic vascular changes in healthy eyes. Choroidal thickness did not depend upon the hydration status for the subjects participating in this study.